PWE-277 Results of an 'opt-out' laparoscopic approach to colorectal cancer resections and factors influence opting out and conversion. (22nd June 2015) - Torrance, A; Evans, R; Hussain, A; Tsiamis, A
Abstract : Introduction: The incidence of laparoscopic colorectal cancer surgery has been increasing year on year in the UK. The 2014 NBOCAP showed 45% of all resections were completed laparoscopically with a conversion rate of 9.6% although variation still exists across the country. At our institution, all colorectal resections are attempted by laparoscopic approach unless deemed inappropriate at MDT discussion. This study aims to review the success of this "laparoscopic first" approach in elective resections and identify factors that my influence conversion rate. Method: A retrospective review of a prospectively maintained database of all colorectal cancer resections from 01/03/2013 – 31/10/2014 was performed. Data was colected on patient age, gender, BMI, co-morbidity (including previous abdominal surgery), colorectal MDT outcome, surgeon/patient preference of approach, initial surgical approach, conversion and reason for conversion. Results: 201 colorectal cancer resections were identified. 164 (81.6%) were elective cases and all of these were discussed pre-operatively at colorectal MDT. 141 (86%) procedures were planned and started laparoscopically with conversion to an open procedure in 10 (6.1%) cases. Overall, 80% of cases were completed laparoscopically. MDT planned for open procedure in 23 (14%) elective cases. Reasons for this were because of advanced tumour size/stage in 10 (43.5%) patients, other pathology requiring surgery in 7 (30.4%) patients (hysterectomy for cancer, gastrectomy for cancer, abdominal aortic aneurysm, suspected Crohn's disease on staging investigations), an obstructing tumour in 2 (8.7%) patients and surgeon preference in 4 (17.4%) patients. Elective conversion was due to adhesions in 6 (60%) patients, a bulky/locally advanced tumour in 2 (20%) patients and a narrow pelvis in 2 (20%) patients. No difference was demonstrated in conversion rate according to age, obesity or gender. Conclusion: We have demonstrated that eighty per cent of our patients were able to undergo laparoscopic resection of their colorectal cancer using this 'opt-out' laparoscopic-first approach. By considering previous surgery, large or locally invasive tumours and coexisting pathology need for conversion can also be limited. Disclosure of interest: None Declared.